2020
DOI: 10.3390/pharmaceutics12050478
|View full text |Cite
|
Sign up to set email alerts
|

Caffeic Acid Phenethyl Ester Assisted by Reversible Electroporation—In Vitro Study on Human Melanoma Cells

Abstract: Melanoma is one of the most serious skin cancers. The incidence of this malignant skin lesion is continuing to increase worldwide. Melanoma is resistant to chemotherapeutic drugs and highly metastatic. Surgical resection can only be used to treat melanoma in the early stages, while chemotherapy is limited due to melanoma multi-drug resistance. The overexpression of glutathione S-transferase (GST) may have a critical role in this resistance. Caffeic acid phenethyl ester (CAPE) is a natural phenolic compound, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 32 publications
(35 reference statements)
0
5
1
Order By: Relevance
“…Furthermore, CAPE was shown to suppress the growth of melanoma (most serious skin cancers that often show drug resistance and high metastatic ability) cells by induction of oxidative stress. Electroporation of melanoma cells with CAPE was suggested as an efficient delivery system [ 48 ]. In line with these reports, we found that like CAPE, whereas high doses of ARC offer anticancer activity [ 33 ], low doses possess antistress (oxidative, metal, and hypoxia) activity.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, CAPE was shown to suppress the growth of melanoma (most serious skin cancers that often show drug resistance and high metastatic ability) cells by induction of oxidative stress. Electroporation of melanoma cells with CAPE was suggested as an efficient delivery system [ 48 ]. In line with these reports, we found that like CAPE, whereas high doses of ARC offer anticancer activity [ 33 ], low doses possess antistress (oxidative, metal, and hypoxia) activity.…”
Section: Discussionmentioning
confidence: 99%
“…As was demonstrated, PEF protocols decreased GSSH and stimulated ROS release in resistant cells. Our previous study showed that electroporation combined with caffeic acid phenethyl ester could also decrease the glutathione ratio in human melanoma cells [ 30 ]. In cancer therapy, doxorubicin delivery is problematic, particularly in drug-resistant cancers, which overexpress MDR-related proteins in cell membranes.…”
Section: Discussionmentioning
confidence: 99%
“…The previously reported in vivo and in vitro studies indicated the anticancer potential of these natural compounds on BRAF or EGFR-related cancer, however, their mechanism of action has not been resolved ( Cohen et al., 2012 ; Choromanska et al., 2020 ; Dutta et al., 2019 ; Wu et al., 2011 ; Kunimasa et al., 2017 ). Our previously published computational study explored the ATP-competitive potential of test compounds for different mutant forms of EGFR ( Malik et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Further, a combination of Wi-A and Sorafenib has been shown to have a synergistic effect against papillary and anaplastic cancer cell lines via caspase-3 and PARP (Poly (ADP-ribose) polymerase cleavage, downregulation of BRAF and inhibition of heat shock proteins ( Cohen et al., 2012 ). Additionally, the combination of CAPE and electroporation has been found to be effective against wild type and V600E mutant melanoma cell lines ( Choromanska et al., 2020 ). In spite of the existing evidence that these natural molecules could inhibit the BRAF-related activation of cancer cell proliferation, none of the studies have shown their binding kinetics against wild type and mutant BRAF proteins.…”
Section: Introductionmentioning
confidence: 99%